Design thinking in applied informatics: what can we learn from Project HealthDesign?. (18th June 2021) - Novak, Laurie L; Harris, Joyce W; Koonce, Taneya Y; Johnson, Kevin B
Abstract: Objective: The goals of this study are to describe the value and impact of Project HealthDesign (PHD), a program of the Robert Wood Johnson Foundation that applied design thinking to personal health records, and to explore the applicability of the PHD model to another challenging translational informatics problem: the integration of AI into the healthcare system. Materials and Methods: We assessed PHD's impact and value in 2 ways. First, we analyzed publication impact by calculating a PHD h-index and characterizing the professional domains of citing journals. Next, we surveyed and interviewed PHD grantees, expert consultants, and codirectors to assess the program's components and the potential future application of design thinking to artificial intelligence (AI) integration into healthcare. Results: There was a total of 1171 unique citations to PHD-funded work (collective h-index of 25). Studies citing PHD span medical, legal, and computational journals. Participants stated that this project transformed their thinking, altered their career trajectory, and resulted in technology transfer into the commercial sector. Participants felt, in general, that the approach would be valuable in solving contemporary challenges integrating AI in healthcare including complex social questions, integrating knowledge from multiple domains, implementation, and governance. Conclusion: Design thinking is a systematic approach to problem-solving characterized by cooperation and collaboration. PHD generated significant impacts as measured by citations, reach, and overall effect on participants. PHD's design thinking methods are potentially useful to other work on cyber–physical systems, such as the use of AI in healthcare, to propose structural or policy-related changes that may affect adoption, value, and improvement of the care delivery system.